Breastfeeding: Short and Long-Term Benefits to Baby and Mother - Wheeler, Ben (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Breastfeeding is the preferred method of feeding in early life. It is also one of the most cost-effective childhood survival interventions. Breastfeeding practices are important for preventing child mortality and morbidity, as well as ensuring the optimal growth, health, and development of infants. The public health benefits of breastfeeding have been well documented in the medical literature, and include the following: associations with decreased risk for early-life diseases such as otitis media, respiratory tract infection, diarrhoea, and early childhood obesity (to name but a few). This Special Issue book includes a collection of studies on the use of novel methods to improve breastfeeding rates, and research exploring the short- and long-term benefits of breastfeeding for both the infant and mother, including technology-based approaches.